Real life efficacy and tolerability of Tenofovir Alafenamide Fumarate in patients with hepatitis-B virus-related cirrhosis - Yapali, Suna; Gokcan, Hale; Durak, Serdar; Ellik, Zeynep Melekoglu; Guzelbulut, Fatih; Vatansever, Sezgin; Ari, Derya; Mehdiyev, Shahin; Adanir, Haydar; Koc, Elif Sitre; Gunduz, Feyza; Arslan, Mehmet; et al. (ELSEVIER, 2022)
International Liver Congress, London, ENGLAND, JUN 22-26, 2022